GENERAL DESCRIPTION, ETIOLOGY, EPIDEMIOLOGY, PREVENTION AND IMPROVEMENT OF ANTI-EPIDEMIC MEASURES OF MEASLES, RUBELLA AND RUBELLA (Лучшие интеллектуальные исследования, 2024)
This article provides a comprehensive overview of the diseases measles, rubella, and scarlet fever, including their etiology, epidemiology, and prevention. It emphasizes the importance of modernizing preventive measures and enhancing epidemic control strategies to minimize their public health impact. The article also discusses vaccination, public health policies, and educational campaigns as critical tools in combating these infectious diseases